Development of a productive research culture in emergency medicine: Report of the outcomes of a research forum. (26th November 2015) - Taylor, David McD; Cohen, Donna R; Epstein, Joseph; Freeman, Peter; Gosbell, Andrew D; Judkins, Simon; Mowatt, Elizabeth JM; O'Reilly, Gerard M; Vinen, John
Abstract: In recent years, the Australasian College for Emergency Medicine (ACEM) has increasingly focused on the need for high‐quality research in emergency medicine (EM). One important initiative was the establishment of the ACEM Foundation, which among other responsibilities, is required to support clinical research through the provision of research funding and other measures. In February 2015, the Foundation held a Research Forum that was attended by the leading EM researchers from Australasia. The Forum aimed to determine how a productive research culture could be developed within the ACEM. Nine key objectives were determined including that research should be a core business of the ACEM and a core activity of the EM workforce, and that EM research should be sustainable and adequately supported. This report describes the background and conduct of the Forum, its recommendations and the way in which they could be implemented.